(untitled) (inOpera Esercizi di lettura su testi contemporanei, 2025)
After an introduction outlining the main historical, theoretical, and methodological issues related to the concept of «recorded authorial diction», the essay focuses on Vittorio Sereni, retracing his most significant experiences in the field of literary phonography, as well as his personal relationship with poetic diction. It then examines a public recording (dating from July 1967) of the first part of Un posto di vacanza. This audio document becomes the subject of a stylistic and performative analysis, in which the poet’s main compositional and performative strategies are brought to light through a systematic comparison between the written and the spoken text.